Activation cross sections for 13.6 MeV neutron induced reactions on natural tin. (June 2022) - Liu, B.; Tian, G.; Yang, X.; Shi, F.; Han, R.; Huang, Y.; Li, X.; Chen, Z.; Lan, C.; Luo, P.; Zhang, X.; Sun, H.; et al.
Abstract: Cross sections of the 112 Sn(n, x) 111 In, 114 Sn(n, 2n) 113 Sn, nat Sn(n, x) 117m Sn and 124 Sn(n, 2n) 123g Sn reactions have been measured by using the activation technique at 13.6 MeV neutron energy. The neutrons were produced via the 3 H(d, n) 4 He reaction. The present experimental data illustrated satisfactory agreement with most of the available literature data. Experimental data are compared with the corresponding evaluated nuclear data from the ENDF/B-VIII.0, JENDL-4.0/HE, BROND-3.1, CENDL-3.2 and JEFF-3.3 libraries, and the agreement are generally acceptable. Besides, different nuclear level density models have been used for the estimation of the desired excitation functions with TALYS-1.95 code. Highlights: Activation cross sections of neutron induced reactions on tin were measured. Activation formula with changed beam intensity was applied. Reliability of the evaluated nuclear data libraries were verified. Effectiveness of the TALYS-1.95 code with different nuclear level density models were tested.